Are academics adapting to students' technology learning preferences?: A South African study of teaching identities - Novel Lena Folabit; Loyiso Currell Jita (Issues in educational research, 2024)
Traditionally, academics in higher education relied on lectures, seminars, and textbooks for face-to-face instruction. However, technology integration in education has transformed the landscape, enhancing engagement, active learning, and personalised instruction, prompting academics to rethink their teaching methods. Anchored in social constructivist theory, our study explores how students' technological learning preferences impact academics' professional identities. Data from semi-structured interviews with nine academics at the University of the Free State, South Africa, selected through convenience and purposive sampling, were coded and thematically analysed. Our study found that although technology provides innovative curriculum design and collaborative learning benefits as students engage with diverse web-based platforms for personalised learning, academics must reassess their teaching approaches by iteratively balancing traditional and technological approaches. They thereby shift from being knowledge transmitters to learning facilitators, despite their limited digital literacy skills. Therefore, we recommend that all higher education stakeholders and web-based companies work together on practical professional development and mentorship programs. These programs will focus on improving academics' skills in digital literacy and innovation skills relevant to web-based learning spaces.